Effects of Copper Addition on Copper Resistance, Antibiotic Resistance Genes, and intl1 during Swine Manure Composting - Yin, Yanan; Gu, Jie; Wang, Xiaojuan; Song, Wen; Zhang, Kaiyu; Sun, Wei; Zhang, Xin; Zhang, Yajun; Li, Haichao (Frontiers in Microbiology, 2017)
Copper is one of the most abundant heavy metals present in swine manure. In this study, a laboratory-scale aerobic composting system was amended with Cu at three levels (0, 200, and 2000 mg kg-1, i.e., control, Cu200, and Cu2000 treatments, respectively) to determine its effect on the fate of copper resistance genes [copper resistance genes (CRGs): pcoA, cusA, copA, and tcrB], antibiotic resistance genes [antibiotic resistance genes (ARGs): erm(A) and erm(B)], and intl1. The results showed that the absolute abundances of pcoA, tcrB, erm(A), erm(B), and intl1 were reduced, whereas those of copA and cusA increased after swine manure composting. Redundancy analysis showed that temperature significantly affected the variations in CRGs, ARGs, and intl1. The decreases in CRGs, ARGs, and intI1 were positively correlated with the exchangeable Cu levels. The bacterial community could be grouped according to the composting time under different treatments, where the high concentration of copper had a more persistent effect on the bacterial community. Network analysis determined that the co-occurrence of CRGs, ARGs, and intI1, and the bacterial community were the main contributors to the changes in CRGs, ARG, and intl1. Thus, temperature, copper, and changes in the bacterial community composition had important effects on the variations in CRGs, ARGs, and intl1 during manure composting in the presence of added copper.